Temporalis Fascia and Free Post‐Aural Soft Tissue Graft in Sub‐Centimeter Skull Base Defect Repair - Vijay Bidkar; Khadeeja K (Journal of Rhinology)
Skull base defects often manifest as meningocele/meningoencephalocele or cerebrospinal fluid (CSF) leaks. Ventral and lateral skull base defects are effectively treated endoscopically and microscopically using various approaches. This case series study analyzes the utility and efficacy of post-aural soft tissue and temporalis fascia grafts in repairing small (<1 cm) skull base defects. Five out of six patients (83.33%) achieved successful defect closure. Patients were followed for donor site morbidity, postoperative CSF leak, and/or recurrent meningocele. One patient experienced reconstruction failure and developed a CSF leak eight months after surgery. The results suggest that TF grafts combined with post-aural soft tissue may be effectively used to repair small skull base defects without significant donor site morbidity.